Popular Science As A Text Genre: a narrative literature review (REMUNOM, 2023)
Science, in addition to being an intellectual and investigative enterprise, is also a rhetorical enterprise as it depends on effective communication practices. Scientific communication comprises three main categories of discourses: primary scientific (esoteric, aimed at the initiated), didactic (for educational purposes), and those for scientific dissemination, called popular science, intended for a "broad" public. In this work, we aimed to examine the discourse of popular science texts, considering it as a text genre. To achieve this, we conducted bibliographical research to support a narrative review of the theme. The review consists of three parts: the first analyzes the trajectory of popular science; the second discusses the discursive and rhetorical prescriptive characteristics of popular science; and finally, the third part explores mostly analytical studies that identify the actual discursive and rhetorical characteristics of popular science as a text genre. The conclusion is that the rhetorical prescriptions of popular science are insufficient to fully describe its discursive characteristics in practice. Furthermore, there is a significant diversity of discourses within this text genre, necessitating classification into subgenres. This is due to the various forms of discursive reformulation used before the primary scientific discourse, which vary significantly among them.